2015
DOI: 10.4028/www.scientific.net/amm.802.89
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Non – Engineered Buildings Roofing System Failure under Wind Loads

Abstract: Strong wind is an annual natural hazard in Malaysia due to the geographical location. The northeast monsoon season usually commences in early November and ends in March. During this season, steady easterly or northeasterly winds of 10 to 20 knots prevail. The strong wind events such as hurricane and storms often caused severe damage to the large number of low rise building especially at the roofing system. At end of year 2014, the series of thunderstorm hit the Northern area of Peninsular Malaysia and caused m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Past damage investigations for windstorm events have revealed factors in poor building performance, particularly in the case of non-engineered rural houses in Malaysia. Several studies have reported that windstorm caused greatest catastrophic damages to rural homes in Malaysia that occurred with failure of roof connections and roof uplift (Deraman et al, 2019;Zaini et al, 2017;Muhammad et al, 2015;Ramli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Past damage investigations for windstorm events have revealed factors in poor building performance, particularly in the case of non-engineered rural houses in Malaysia. Several studies have reported that windstorm caused greatest catastrophic damages to rural homes in Malaysia that occurred with failure of roof connections and roof uplift (Deraman et al, 2019;Zaini et al, 2017;Muhammad et al, 2015;Ramli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These types of buildings are most vulnerable to be damaged during windstorm [1,2,3]. Typically, they were built with a minimum or no structural engineering design compared to other buildings that use codes and standards [4]. In Malaysia, rural houses are considered as non-engineered building, typically built according to the location and culture.…”
Section: Introductionmentioning
confidence: 99%